FINANCIAL DISTRESS ANALYSIS USING THE ALTMAN Z-SCORE METHOD TO PREDICT PT. GARUDA INDONESIA TBK FOR THE 2021-2024 PERIOD - Resha Try Piskah; Pascuela Dearaujo Pana'da; Clemensia Meilani (Jurnal Mahasiswa Manajemen, 2026)
The purpose of this study is to identify and analyze financial distress using the Altman Z-score method to predict bankruptcy at PT. Garuda Indonesia, Tbk. The data collection technique used in this study is documentation, which is an effort to obtain data through recording documents/archives or other evidence related to the research. The data analysis used in this study is quantitative dasta analysis, which is a data analysis technique that uses numerical calculations from financial statements. The analysis technique used in this study is the Altman Z-Score Model. The results of the financial distress analysis using the Altman Z-Score method to predict bankruptcy at PT. Garuda Indonesia, Tbk indicate that over the four years from 2021 to 2024, the company was classified as healthy. This is evident from the Z-score results for PT. Mayora Indah, Tbk, which showed a Z-score > 2.9, indicating that PT. Garuda Indonesia, Tbk was categorized as a healthy company for each study period.